Public Participation in Transport in Times of Change - Hansson, Lisa; Hedegaard Sørensen, Claus; Rye, Tom (Emerald Publishing Limited, 2023)
The role and agency of the public is often a minor consideration for researchers, authorities, and other experts evaluating policy goals, strategies, and instruments within the transport sector. Public Participation in Transport in Times of Change analyses and discusses different forms of participation, challenges, and lessons to be learned across the field. Chapters discuss various forms of public participation in connection to sustainable mobility, transport planning, policy packaging, health, infrastructure, and active travel, creating a comprehensive analysis relevant for both practitioners and researchers who operate within the transport field. The Transport and Sustainability series addresses the important nexus between transport and sustainability containing volumes dealing with a wide range of issues relating to transport, its impact in economic, social, and environmental spheres, and its interaction with other policy sectors.
Keywords: Transportation -- Planning -- Citizen participation.; Transportation and state.; Transportation -- General.; Transport planning & policy.; elektronické knihy; electronic books